Healthcare-associated Crimean-Congo haemorrhagic fever in Turkey, 2002–2014: a multicentre retrospective cross-sectional study. (April 2016) - Leblebicioglu, H.; Sunbul, M.; Guner, R.; Bodur, H.; Bulut, C.; Duygu, F.; Elaldi, N.; Cicek Senturk, G.; Ozkurt, Z.; Yilmaz, G.; Fletcher, T.E.; Beeching, N.J.
Abstract: Healthcare-related transmission of Crimean-Congo haemorrhagic fever (CCHF) is a well-recognized hazard. We report a multicentre retrospective cross-sectional study undertaken in Turkey in 2014 in nine hospitals, regional reference centres for CCHF, covering the years 2002 to 2014 inclusive. Data were systematically extracted from charts of all personnel with a reported health care injury/accident related to CCHF. Blood samples were tested for CCHF IgM/IgG by enzyme-linked immunosorbent assay and/or viral nucleic acid detection by PCR after the injury. Fifty-one healthcare-related exposures were identified. Twenty-five (49%) of 51 resulted in laboratory-confirmed infection, with a 16% (4/25) overall mortality. The main route of exposure was needlestick injury in 32/51 (62.7%). A potential benefit of post-exposure prophylaxis with ribavirin was identified.